KONSEP PEMBUDAYAAN KARAKTER RELIGIUS DI SEKOLAH (STUDI TENTANG UPAYA MEMBANGUN IKLIM SEKOLAH YANG KONDUSIF) - Nelly, Nelly (Jurnal Bilqolam Pendidikan Islam, 2021)
This paper is aimed at examining conceptually the efforts to build conducive school climate based on religious character culture. Conducive school climate is a condition and atmosphere of school climate with all supporting components both human resources and existing facilities to provide safety and convenient experience for all school residents with various activities both material and spiritual. Building conducive school climate is a maximum effort for school residents to create a harmonious education and learning climate actualized in the form of a safety feeling, convenient, family climate as a supporting factor for the process of learning activities, which is effective, efficient, and productive. Building a conducive school climate can be realized through the effort to create safety feeling, comfortable and beautifully. It is an environmental condition providing school atmosphere with high effectiveness. Meanwhile, the religious characters becoming the foundation of conducive school climate are faith, devotion, honesty, modeling, democratic atmosphere, care, openness, togetherness, safety, orderly, cleanness, politeness,  beauty, and health